2021
DOI: 10.1101/2021.01.28.428430
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulation of blood–brain barrier integrity by microbiome-associated methylamines and cognition by trimethylamineN-oxide

Abstract: Communication between the gut microbiota and the brain is primarily mediated via soluble microbe-derived metabolites, but the details of this pathway remain poorly defined. Methylamines produced by microbial metabolism of dietary choline and L-carnitine have received attention due to their proposed association with vascular disease, but their effects upon the cerebrovascular circulation have not hitherto been studied. Here we use an integrated in vitro/in vivo approach to show that physiologically relevant con… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 103 publications
(147 reference statements)
0
6
0
Order By: Relevance
“…[27] Now, some researches have noticed the effects of TMA, especially in cardiovascular health. [4,7,[28][29][30][31] And, some influential studies have pointed out that inhibiting the production of TMA by intestinal microorganisms is a potential way to treat cardiovascular diseases, which partially proves the importance of gut microbiota metabolite TMA. [32][33][34] To find an answer to the scientific question about the role of gut microbial metabolite TMA in the effects of TMAO on glucose and lipid metabolism, i.p., TMAO was applied to avoid the gut microbiota and to compare with oral TMAO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27] Now, some researches have noticed the effects of TMA, especially in cardiovascular health. [4,7,[28][29][30][31] And, some influential studies have pointed out that inhibiting the production of TMA by intestinal microorganisms is a potential way to treat cardiovascular diseases, which partially proves the importance of gut microbiota metabolite TMA. [32][33][34] To find an answer to the scientific question about the role of gut microbial metabolite TMA in the effects of TMAO on glucose and lipid metabolism, i.p., TMAO was applied to avoid the gut microbiota and to compare with oral TMAO.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a few studies have reported that TMA can also cause adverse effects on physical health, including increased arterial blood pressure, increased gestational diabetes mellitus risk, decreased vascular smooth muscle cells viability, and impaired blood-brain barrier function due to disrupted tight junction integrity. [4][5][6][7] So, it is still unclear about the role of gut microbiota metabolite TMA in the effects of TMAO on the possible adverse health effects. In this study, to investigate the role of gut microbial metabolite TMA in the effects of TMAO on glucose and lipid metabolism, C57BL/6J mice were fed a high fat diet with oral or intraperitoneal (i.p.)…”
Section: Introductionmentioning
confidence: 99%
“…Neuroprotective effects of TMAO have also been documented in in vitro studies of other neurologic conditions, including amyotrophic lateral sclerosis and Machado-Joseph disease/spinocerebellar ataxia-3 (C. R. Brown et al, 1996;Getter et al, 2015;Yoshida et al, 2002). Moreover, under physiological concentrations, it has been reported that TMAO promoted blood-brain barrier integrity, whereas its precursor, TMA, disrupted tight junctions of the blood-brain barrier (Hoyles et al, 2021). These conflicting results could be due to the fact that TMAO simply facilitates protein folding, whereas the specific folding patterns (i.e.…”
Section: Effect Of Tmao On Astrocyte Activationmentioning
confidence: 92%
“…Chronic low-dose TMAO influences inflammatory variables, such as TNF and IL-1. However, it reverses LPS-induced BBB damage and memory impairment, prevents the degradation of cell structural arrangement, lowers oxidative stress, and preserves the integrity of cerebrovascular endothelial cells (113). Nonetheless, in ICH, a high blood concentration of TMAO may exacerbate cellular inflammation by activating microglia and astrocytes (114).…”
Section: Bidirectional Interaction Of Microbial Metabolites After Cevdmentioning
confidence: 99%